Some uses and misuses of research for criminal justice policy development and utilization - Hippchen, Leonard J. (American journal of criminal justice, 1981)
Criminal justice research has been extensively critized In recent years for its may shortcomings. Problems In its use appear to focus around three major areas of effort: Policy-makers, research managers, and professional researchers. This paper reviews what are seen as some of the major obstacles to quality criminal justice research in each of these areas of contemporary concern. Then, a number of suggestions are offered which are designed to improve the use of research for policy development and utilization in criminal justice.